Hyperoodon (Frasercetus) planifrons Flower 1882 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Hyperoodon (Frasercetus) planifrons Flower 1882 Hyperoodon (Frasercetus) planifrons Flower 1882, Proc. Zool. Soc. Lond., 1882: 392. Type Locality: "found upon the sea-beach of Lewis Island in the Dampier Archipelago, north-western Australia.". Vernacular Names: Southern Bottlenose Whale. Synonyms: Hyperoodon (Frasercetus) burmeisterei Moreno 1895. Distribution: Southern hemisphere: circumpolar, antarctic to temperate waters, rarely into tropical waters. May occur in the W North Pacific. Conservation: CITES – Appendix I; IUCN – Lower Risk (cd). Discussion: Reviewed by J. G. Mead (1989 b ). Moore (1968) erected the subgenus Frasercetus for this species. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 740, DOI: 10.5281/zenodo.7316519